Non-uniformity of Clinical Head, Head and Neck, and Body Coils in Magnetic Resonance Imaging (MRI) - Mahmood Nazarpoor (Iranian Journal of Medical Physics, 2014)
Introduction Signal intensity uniformity in a magnetic resonance (MR) image indicates how well the MR imaging (MRI) system represents an object. One of the major sources of image non-uniformity in high-field MRI scanners is inhomogeneity of radio-frequency coil. The aim of this study was to investigate non-uniformity in head, head and neck, and body coils and compare the obtained results to determine the best clinical coil for future clinical application. Materials and Methods A phantom was designed to investigate the non-uniformity of coils. All evaluations were carried out using a 1.5 T clinical MRI scanner. T1-weighted inversion recovery sequence (linear phase encoding) and turbo fast low angle shot (TurboFLASH) images were used to find non-uniformity in the clinical coils. For testing the uniformity of coils, signal intensity profiles in parts of the coronal image of phantom were measured over X and Y axes. Results The results showed that body coil was the most uniform coil of all; in addition, the head and neck coil was more uniform than the head coil. The results also indicated that signal-to-noise ratio (SNR) of the head and neck coil was higher than the head and body coils. Moreover, SNR of the head coil was higher than that of the body coil. Conclusion In order to accurately find or apply an image signal intensity for measuring organ blood flow or perfusion, coil non-uniformity corrections are required.